Mitwirkung der Raumordnung bei der Bestimmung von FFH-und Europäischen Vogelschutzgebieten - Schmidt, Albert (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The transposition into national law of the EU's FFH and Conservation of Wild Birds Derective has involved the introduction of a number of new duties and legal consequences (such as environmental impact assessments, protection of habitats and prohibitions on inpairment) affecting conservation and regional planning. The first part of this article is concerned with duties of notification and protection and with EIAs for projects and plans, and with the technical criteria and procedure for selecting areas for the “Natura 2000” network. The second part of the article discusses ways in which the goals of regional planning should be taken into account in selecting suitable sites, the implementation of Natura 2000 within state development plans and regional plans, and the pros and cons of a spatial-planning-oriented procedure.